Affective temperaments play an important role in the relationship between childhood abuse and depressive symptoms in major depressive disorder. (28th February 2016) - Toda, Hiroyuki; Inoue, Takeshi; Tsunoda, Tomoya; Nakai, Yukiei; Tanichi, Masaaki; Tanaka, Teppei; Hashimoto, Naoki; Takaesu, Yoshikazu; Nakagawa, Shin; Kitaichi, Yuji; Boku, Shuken; Tanabe, Hajime; et al.
Abstract: Previous studies have shown that various factors, such as genetic and environmental factors, contribute to the development of major depressive disorder (MDD). The aim of this study is to clarify how multiple factors, including affective temperaments, childhood abuse and adult life events, are involved in the severity of depressive symptoms in MDD. A total of 98 participants with MDD were studied using the following self-administered questionnaire surveys: Patient Health Questionnaire-9 measuring the severity of depressive symptoms; Life Experiences Survey (LES) measuring negative and positive adult life events; Temperament Evaluation of the Memphis, Pisa, Paris, and San Diego auto-questionnaire (TEMPS-A) measuring affective temperaments; and the Child Abuse and Trauma Scale (CATS) measuring childhood abuse. The data were analyzed using single and multiple regression analyses and structural equation modeling (SEM). The neglect score reported by CATS indirectly predicted the severity of depressive symptoms through affective temperaments measured by TEMPS-A in SEM. Four temperaments (depressive, cyclothymic, irritable, and anxious) directly predicted the severity of depressive symptoms. The negative change in the LES score also directly predicted severity. This study suggests that childhood abuse, especially neglect, indirectly increases the severity of depressive symptoms through increased scores of affective temperaments in MDD. Highlights: We examine childhood abuse, temperaments, and stressful life events in MDD. Childhood abuse increases affective temperaments in adulthood. Temperaments predict the severity of depressive symptoms. Childhood abuse predicts depressive symptoms through affective temperaments.